Greater Expectations: An Appreciative Inquiry into How UK Home-Educating Families Support Their Children's Learning - Kaili C. Zhang (MDPI AG, 2024)
Elective home education is a significant aspect of the UK educational system, yet dedicated research on this topic is limited. This study, employing Appreciative Inquiry, explored the best practices perceived by 90 UK home-educating parents. It uncovered diverse strategies, emphasising the importance of resources such as technology, curricula, and collaborative efforts within home education co-operatives. Parents stressed the value of flexible learning environments and strong family commitment, envisioning a future with an enhanced home learning atmosphere and government and school support. They recommended concrete guidance for prospective home-educating parents, focusing on comprehensive child development. Ultimately, families aspired to shape a future for home education that prioritises enriched learning environments, broader societal recognition, and practical support for those embarking on the home education journey. The study's findings have implications for children's development, facilitating collaboration between homes and schools, as well as partnerships between families and educators.